Gender and Space in Literature and Cinema (Bogomil Rainov’s Roads to Nowhere and Metodi Andonov’s A White Room) - Nyagolova, Natalya (Slavica, 2021)
The article discusses the structural link between the gender model and the fictional space in Bogomil Rainov’s short story Roads to Nowhere (1966) and its film adaptation—Metodi Andovov’s A White Room (1968). The transformations of the original text are traced via several semantic oppositions (masculine-feminine, rational-emotional, order-chaos) and the influence of two aesthetic paradigms—noir and the existentialist “new wave”. These transformations are interpreted in the socio-cultural context of the Bulgarian “thaw” with its quest for the marginal, regional, personal alternatives within the socialist system.